Depressive symptoms and childhood sleep apnea syndrome - Carotenuto M (Dove Medical Press, 2012)
Marco Carotenuto,1 Maria Esposito,1 Lucia Parisi,2 Beatrice Gallai,3 Rosa Marotta,4 Antonio Pascotto,1 Michele Roccella21Sleep Clinic for Developmental Age, Clinic of Child and Adolescent Neuropsychiatry, Second University of Naples, Naples, Italy; 2Child Neuropsychiatry, Department of Psychology, University of Palermo, Palermo, Italy; 3Unit of Child and Adolescent Neuropsychiatry, University of Perugia, Perugia, 4Department of Psychiatry, "Magna Graecia" University of Catanzaro, Catanzaro, ItalyBackground: The relationship between sleep and mood regulation is well known, and some reports suggest a key role of sleep-related breathing disorders (SRBD) in the development of the symptomatology of depression, even if no conclusive data are actually found in the clinical literature. The aim of this study was to assess the relationship between SRBD and depressive symptoms in a population of school-aged children.Methods: The study population comprised 94 children affected by SRBD and 107 healthy children. To identify the severity of SRBD, an overnight respiratory evaluation was performed. All subjects filled out the Italian version of the Children Depression Inventory (CDI) to screen for the presence of depressive symptoms.Results: The group with SRBD showed higher CDI scores than the group without SRBD, with a positive correlation found between CDI scores, apnea-hypopnea index, and oxygen desaturation index values. Logistic regression showed that an apnea-hypopnea index ≥ 3 and an oxygen desaturation index ≥ 1 could be risk factors for development of depressive symptoms. According to receiver-operating characteristic curve analysis, the cutoff point for the apnea-hypopnea index that could cause a pathological CDI score (≥19) was >5.66, and the cutoff point for the oxygen desaturation index was >4.2. The limitations of this study are that our data are derived from one single psychometric test and not from a complete psychiatric evaluation, and our subjects came from a small group in southern Italy.Conclusion: Our results suggest the importance of mood assessment in children affected by SRBD.Keywords: depression, sleep-related breathing disorders, cardiorespiratory monitoring, children